1987
DOI: 10.1111/j.1600-0722.1987.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy of early microbial colonization of human enamel and root surfaces in vivo

Abstract: – This study describes the early microbial colomization of teeth by the use of light‐and transmission electron microscopy. Six dental students carried a total of 60 test pieces of unerupted enamel and root surface in intraoral acrylic appliances for 4, 8, 12, 24 and 48 h, during which periods oral hygiene was abandoned. Pronounced variations were recorded in structure and thickness of the pellicle across the individual surfaces of both dental tissues. Bacterial single‐cell colonization increased the electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0
5

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 39 publications
7
29
0
5
Order By: Relevance
“…Although these numbers are 10-to 100-fold lower than total counts reported in previous studies (25), the increase in cell numbers between 4 and 8 h in the present study and in reference 24 was strikingly similar: 2-to 40-fold. Collectively, the relative amounts of colonization at 4 and 8 h and the relative ratios of actinomyces to strepto- cocci at 4 and 8 h, as well as the predominance of streptococci in early dental plaque, support and extend previous work (21)(22)(23)25).…”
Section: Discussionsupporting
confidence: 72%
“…Although these numbers are 10-to 100-fold lower than total counts reported in previous studies (25), the increase in cell numbers between 4 and 8 h in the present study and in reference 24 was strikingly similar: 2-to 40-fold. Collectively, the relative amounts of colonization at 4 and 8 h and the relative ratios of actinomyces to strepto- cocci at 4 and 8 h, as well as the predominance of streptococci in early dental plaque, support and extend previous work (21)(22)(23)25).…”
Section: Discussionsupporting
confidence: 72%
“…Plaque biovars were seen to develop at exactly the same rate from individual to individual, reaching a plateau around 12 hours after stent insertion (Nyvad & Kilian, 1987). Electron microscopy confirmed a change in species composition over the next 12 hours with both Gram-positive and Gram-negative bacteria appearing, providing evidence for direct interaction between species in the biofilm (Nyvad & Fejerskov, 1987b). Further studies confirmed the importance of cell-to-cell recognition in early plaque development and examination of undisturbed plaque.…”
Section: Bacterial Interactions During Biofilm Developmentsupporting
confidence: 56%
“…The proximity of phenotypes allows for their interactions and influences their ability to survive within the biofilm. Among the early studies of spatial relationships in plaque biofilm formation are the studies by Nyvad and colleagues (Nyvad, 1993;Nyvad & Fejerskov, 1987a;Nyvad & Fejerskov, 1987b;Nyvad & Killian, 1987). Using a stent that holds enamel pieces (commonly used in supragingival oral film investigations), they placed it in the oral cavity and monitored the formation of plaque biofilms.…”
Section: Bacterial Interactions During Biofilm Developmentmentioning
confidence: 99%
“…With increasing age of the biofilm, microcolonies of A. naeslundii and other non-streptococci were seen to extend perpendicularly from the supporting surface as 'chimney' structures and palisades like those observed by electron microscopy of multi-layered dental plaque (Listgarten et al, 1975;Nyvad & Fejerskov, 1987b;Rosan et al, 1976). The morphogenesis of these particular structures can only be speculated on.…”
Section: Discussionmentioning
confidence: 99%
“…For the first time, our study provides a presentation of the spatio-temporal organization of A. naeslundii in relation to other bacteria in initial multi-layer dental biofilms formed in vivo up to 48 h and definitively demonstrates that A. naeslundii preferentially occupies the inner part of early multilayered biofilms. We therefore infer that the densely packed, pleomorphic Gram-positive bacteria with thick cell walls previously observed close to the enamel surface in electron micrographs (Listgarten et al, 1975;Nyvad & Fejerskov, 1987b;Schroeder & De Boever, 1970) are A. naeslundii.…”
Section: Discussionmentioning
confidence: 99%